Global projects: a bibliometric study of international business journals - Battistuzzo, Flávio Jorge; Piscopo, Marcos (Internext, 2015)
Project management is an important process for the implementation of strategies. Different organizations use these concepts and tools to deploy strategies and acquire and sustain competitive advantages. Its importance to the proper execution of strategies has received the attention of different scholars. In line with project management, global projects have some specificities that make them more difficult to manage, as foreign liability and cultural issues. As the success of strategies and organizations themselves are linked to the success of projects, to understand global projects means to understand how management theory can be applied to project management in order to make organizations more successful. This bibliometric study aims to identify current trends in the global projects literature and evaluate its state of the art. Our conclusion indicates a concentration of papers on institutional theory, risk analysis/decision process and project marketing. We believe our study can support and encourage scholars to research the existing clusters identified by this study and evaluate how organization theory can be applied to the management of global projects.